Analisis Peran Latar Belakang Pendidikan Instruktur Dalam Pembentukan Kompetensi Dasar Siswa Bintara Polri di SPN Polda Lampung - Vivi Yuliantari Zanera; Saptarini Saptarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of instructors’ educational backgrounds in the formation of basic competencies among Police Non-Commissioned Officer (NCO) cadets at the State Police School of the Lampung Regional Police. Variations in instructors’ educational levels, namely senior high school, bachelor’s, and master’s degrees, are assumed to influence teaching methods, guidance, and learning effectiveness. This research employed a qualitative phenomenological approach to explore the experiences of instructors and cadets. Data were collected through in-depth interviews, observation, and documentation involving ten informants, consisting of five instructors and five Police NCO cadets. The findings indicate that instructors with bachelor’s and master’s degrees tend to deliver learning materials in a more systematic and conceptual manner, while instructors with a senior high school background emphasize field experience, practical training, and the development of discipline and mental resilience. The formation of basic competencies is carried out in an integrated manner through theoretical learning, practical activities, physical training, and mental development. Determining factors of instructors’ educational background include the relevance of education to teaching subjects, service and teaching experience, instructional methods, availability of facilities and infrastructure, as well as cadets’ motivation and discipline in the national police education process